Seasonal Variation in Transport of Zooplankton Into the Arctic Basin Through the Atlantic Gateway, Fram Strait - Basedow, Sünnje L.; Sundfjord, Arild; von Appen, Wilken-Jon; Halvorsen, Elisabeth; Kwasniewski, Slawomir; Reigstad, Marit (Frontiers in Marine Science, 2018)
The largest contribution of oceanic heat to the Arctic Ocean is the warm Atlantic Water (AW) inflow through the deep Fram Strait. The AW current also carries Atlantic plankton into the Arctic Basin and this inflow of zooplankton biomass through the Atlantic-Arctic gateway far exceeds the inflow through the shallow Pacific-Arctic gateway. However, because this transport has not yet been adequately quantified based on observational data, so that the present contribution is poorly defined, and future changes in Arctic zooplankton communities are difficult to project and observe. Our objective was to quantify the inflow of zooplankton biomass through the Fram Strait during different seasons, including winter. We collected data with high spatial resolution covering hydrography (CTD), currents (ADCP and LADCP) and zooplankton distributions (LOPC and MultiNet) from surface to 1000 m depth along two transects crossing the AW inflow during three cruises in January, May and August 2014. Long-term variations (1997-2016) in the AW inflow were analyzed based on moored current meters. Water transport across the inflow region was of the same order of magnitude during all months (January 2.2 Sv, May 1.9 Sv, August 1.7 Sv). We found a higher variability in zooplankton transport between the months (January 51 kg C s-1, May 34 kg C s-1, August 50 kg C s-1), related to seasonal changes in the vertical distribution of zooplankton. However, high abundances of carbon-rich copepods were observed in the AW inflow during all months. Surface patches with high abundances of C. finmarchicus, Microcalanus spp., Pseudocalanus spp. and Oithona similis clearly contributed to the advected biomass, also in winter. The data reveal that the phenology of species is important for the amount of advected biomass, and that the advective input of zooplankton carbon into the Arctic Basin is important during all seasons. The advective zooplankton input might be especially important for mesopelagic planktivorous predators that were recently observed in the region, particularly during winter. The inflow of C. finmarchicus with AW was estimated to be in the order of 500 000 metric tons C y-1, which compares well to modeled estimates.